Clinical Predictors of Hearing Preservation in Ménière Disease - Fitria Waffi Nur Aini; Mahatma Sotya Bawono; Agus Surono; Feri Trihandoko (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2026)
Hearing outcomes in Ménière disease are heterogeneous, ranging from prolonged fluctuation to irreversible decline and bilateral involvement. Because hearing level influences counselling and follow up planning, clinicians need practical predictors that are available from history taking and routine audiometry. This review summarises evidence published between 2016 and 2025 on clinical predictors associated with hearing preservation in Ménière disease. Across contemporary cohorts and meta analytic data, older age and longer disease duration are repeatedly associated with poorer hearing and a lower likelihood of maintaining serviceable thresholds. Baseline audiometry is the most actionable predictor, earlier stages and low frequency predominant loss show a greater probability of stable or improved thresholds with conservative management, while broader frequency involvement and early high frequency loss are linked to progression and increased risk of bilateral disease. Comorbid migraine and specific clinical phenotypes at onset have also been associated with bilateral involvement. Overall, age, disease duration, baseline stage, frequency pattern of loss, migraine history, and onset phenotypes form a framework for risk stratification and hearing follow up in Ménière disease.